Development of Interactive Learning Media Based on Video Tutorials using the Lectora Inspire and Macromedia Flash Applications in Stone and Concrete Engineering Courses - Zuwida, Nidal; Andreas, Laras Oktavia; Gusmareta, Yuwalitas (CIVED, 2023)
This research aims to create learning media in the Stone and Concrete Engineering course with the help of the Lectora Inspire and Macromedia Flash applications. The approach carried out in this study uses the R&D method using a 4D development model which includes the defining stage (define), design stage (design), development stage (develop) and trial stage (disseminate). The subjects of the study were civil engineering students enrolled in the Stone and Concrete Engineering course as many as 16 people. Assessment of the feasibility of learning media is carried out by providing validity and practicality questionnaires to media experts, material experts. Data from the questionnaire is then processed to determine the level of validity and practicality of the learning media. The effectiveness of learning media is measured from student learning outcomes using developed learning media. The assessment results from media and material experts for learning media made get an average score of 0.86 in the very valid category. The results of the assessment of the practicality of the learning media made get an average score of 86% in the very practical category. Based on the implementation of the pretest, the average score was 58.25 and the implementation of the posttest or final test obtained the average value was 80.12. There is an increase in student learning outcomes after being given video tutorial-based learning media so that it can be concluded that the level of effectiveness of using this media is very effective. Referring to the assessment of material experts, media experts, tests to students can be declared learning media that are developed suitable for use as learning media.